Implementasi Blue Economy Dalam Meningkatkan Kesejahteraan Masyarakat Nelayan Perspektif Maqashid Syariah: (Studi Kasus Pada TPI Brondong) - Shofiyah; Lailatul Azizah (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2023)
Seeing the condition of the fishing community, some of which are still less prosperous, especially fishermen who go to sea once a week, of course many new ideas are needed so that the welfare of fishermen can increase. The presence of the blue economy concept, which is a design for optimizing water resources to increase economic growth in marine areas through creative and innovative activities, namely creating new programs while maintaining environmental sustainability, is expected to be able to improve the economy of fishing communities. This article is intended to find out the extent to which the implementation of the blue economy has improved the welfare of the fishing community at TPI Brondong, especially from a maqashid sharia perspective. The research method used is a descriptive qualitative method which tends to use more inductive analysis and a theoretical basis so that the focus of the research is in accordance with the facts in the field. The results of the research show that there are 2 programs in the implementation of the blue economy at TPI Brondong: 1. Good Fish Handling Methods (CPIB), namely maintaining the quality of fish, namely by paying attention to storage and handling fish properly when landed. 2. Measurable Fish Catching (PIT), namely changing fishing gear from cantrang to JALATONG so that the marine ecosystem is maintained. Because the quality is maintained and the fish caught are dominated by large fish, the selling value of the fish becomes expensive and automatically increases fishermen's income, especially from the perspective of maqashid sharia which shows that fishermen work in accordance with the basic elements or values contained in maqashid sharia which refers more to maintaining or maintaining wealth (Hifdzu Al-Maal).